Fragmentation of the isoscalar giant quadrupole resonance in low mass 12 -< A -> 40 nuclei and 2+ level density in 40Ca from high energy-resolution (p,p') scattering at 200 MeV - Usman, Iyabo Tinuola (My University, 2010)
The Isoscalar Giant Quadrupole Resonance (ISGQR) in low-mass nuclei has been investigated in high energy-resolution experiments using proton inelastic scattering at Ep equals to 200 MeV. The measurements extend and complete the investigation already undertaken for medium and heavy-mass nuclei using the K600 magnetic spectrometer and a proton beam from the K200 Separated Sector Cyclotron (SSC) facility of iThemba LABS, South Africa.